KOMUNIKASI CITY BRANDING “BADUNG THE SOUL OF BALI” UNTUK MEMASARKAN DAYA TARIK WISATA OLEH DINAS PARIWISATA KABUPATEN BADUNG - Sagrario, Johanes; Dewi, LGLK.; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p02, 2024)
One type of tourism marketing in an area is through city branding. Badung Regency has had a city branding with the slogan "Badung the Soul of Bali" since 2018. The Badung Regency city branding was created as a tourism promotion program for Badung Regency. However, in its launch, the public and tourists did not know about the city branding. The purpose of this study is to determine the communication of the city branding "Badung the Soul of Bali", so that it is known to the public and tourists. The data analysis technique used in the results of this study uses descriptive qualitative analysis of city branding communication, primary, secondary, tertiary communication, and internal and external constraints. The type of data used is qualitative and quantitative data, primary and secondary data. Data collection techniques by observation, interviews, documentation, and literature study. The results showed that the city branding program "Badung the Soul of Bali" was in accordance with the concept of city branding communication according to Kavaratzis. However, in this study it was found that the Tourism Office has not been maximal in introducing city branding in Badung Regency, such as not having a logo installed in every tourist attraction, rarely using city branding logos in social media promotions and events that are carried out. From the results of the interview, it is known that the Tourism Office is experiencing problems in funding, cooperation and socialization to the public and tourists.